Neuroinflammatory Disease Responsive to MEK-Inhibitor. (5th December 2022) - Chen, Vicky; Yadav, Vijayshree; Soldatos, Ariane; Cho, Yoon-Jae; Nath, Avindra; Brown, Desmond; Diamond, Eli; Solit, David; Woltjer, Randall; Sayama, Christina; Winer, Jesse; Garavatti, Emily; et al.
Abstract : Objective: Illustrate that some neuroinflammatory diseases may respond best to antiproliferative therapies rather than immunomodulatory therapies. Background: Genomics are increasingly employed in the diagnostic armamentarium of refractory neuro-inflammatory diseases. Metagenomic next-generation sequencing is used to detect pathogens and germline genetic testing is used to detect inborn errors of the immune system. Genetic testing of tissue can identify somatic mutations for targeted treatment. MEK-inhibitors are an emerging treatment for RAS/MAPK pathway mutated diseases which include some neuro-inflammatory mimics like neuro-histiocytoses. Design/Methods: NA. Results: Previously healthy 12-year-old girl presented with 1 month of diplopia and headaches. Her brother has clinically diagnosed NF1 (café-au-lait macules, cutaneous neurofibromas). Exam notable for right third nerve palsy. MRI showed T2/FLAIR hyperintense lesions of the right temporal lobe, basal ganglia, and cervical through thoracic cord, nodular leptomeningeal enhancement along the entire spinal cord, and right middle cerebral artery vessel wall enhancement. CSF: WBC 6/mm 3 (62% lymphocytes 37% monocytes), protein 133 mg/dL. She improved with pulse methylprednisolone and maintenance steroids. At 5 months, she developed malignant elevated intracranial pressure with CSF OP >50 cm water, bradycardia, and encephalopathy requiring weekly LPs. Brain biopsy showed astrocytic and microglial activation without significant inflammation. No histiocytes were noted. There was no evidence of neoplasia or infection. She was tried on anakinra. At 6 months, she developed left third nerve palsy and seizures. For weeks, she required daily LPs for intracranial hypertension despite placement of ventriculoperitoneal shunt. Additional treatments included infliximab, steroids, and siltuximab. NGS from brain biopsy identified 2 NF1 mutations (nonsense, splicing). Allele fractions: 6% and 9%. Her mental status and need for frequent LP improved dramatically with trametinib. Conclusions: This case illustrates the importance of considering somatic genomic testing of neural tissue even when the neuropathology is not suggestive of a malignancy or histiocytosis as this can inform newer molecularly targeted therapeutic options.